Assessment of Urban Heat Island based on the relationship between land surface temperature and Land Use/ Land Cover in Tehran. (May 2016) - Bokaie, Mehdi; Zarkesh, Mirmasoud Kheirkhah; Arasteh, Peyman Daneshkar; Hosseini, Ali
Abstract: In this study, the relationship between land surface temperature (LST) and Land Use/Land Cover (LULC) in Tehran Metropolitan City was studied using Landsat TM satellite image. For this, LST was calculated in accordance with the algorithm (Jiménez-Muñoz & Sobrino, 2003) and the LULC map was prepared based on supervised classification method. According to the LST map obtained by processing the thermal band of the satellite image, areas affected by Urban Heat Island (UHI) were detected to examine their status in relation to the existing LULC classes and the population density. The results showed that UHI created in Tehran are different in terms of the causative agent. This difference is primarily due to the status of LULC in the region and reflects the close relationship between land cover and land surface temperature. Also, the distribution of vegetation and green spaces in different areas of Tehran City was studied by normalized vegetation index (NDVI) using remotely-sensed data. Correlation study between the land cover and land surface temperature showed a negative correlation between these two parameters. Study of the average surface temperature in six LULC classes indicated full compliance of heat islands with LULC classes.